NUMERICAL MODELING OF THERMAL MECHANICAL PROCESSES IN THE MID-OCEANIC RIDGE RIFT ZONES - Galushkin Yu.I.; Dubinin Ye.P.; Sveshnikov A.A.; Ushakov S.A. (My University, 2000)
Analyzed in this paper are the stationary and nonstationary models for the formation of the thermal state of the lithosphere in the axial zones of the mid-oceanic ridges. It is demonstrated that stationary models allow one to analyze the fairly complex two- and three-dimensional integrated models for the formation of thermal conditions in the axial zones, taking into account the processes of melt segregation and migration toward the axial zone, and the formation of the crust and surface topography of the lithosphere. However, the thermal effect of latent basalt melting heat release or absorption is treated in these models using rough approximations. For this reason the stationary models available are not suitable for analyzing the formation of the thermal mechanism of the axial zones of the ridges, as well as the origin and evolution of crustal magma chambers from the time of spreading generation. The model discussed in this paper allows one to reconstruct the transition of the nonstationary temperature field produced by the repeated emplacements of axial, 5 m to 50 m wide intrusions, repeated each 500- to 10000-year periods of time, to a quasi-stationary temperature distribution in the axial zone of the spreading center and to evaluate the conditions for the existence of a crustal magma chamber there.
Keywords: NUMERICAL MODELING; THERMAL MECHANICAL PROCESSES; MID-OCEANIC RIDGE; RIFT ZONES